2017
DOI: 10.1159/000455969
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Promotes Pneumococcal Killing and Modulates Inflammatory Responses in Primary Human Neutrophils

Abstract: Streptococcus pneumoniae is a major human pathogen and a leading cause of pneumonia, septicemia, and meningitis worldwide. Despite clinical studies linking vitamin D deficiency and pneumonia, molecular mechanisms behind these observations remain unclear. In particular, the effects of vitamin D on neutrophil responses remain unknown. Using pneumococcal strains, primary neutrophils isolated from human blood, and sera from patients with frequent respiratory tract infections (RTIs), we investigated the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 38 publications
(37 reference statements)
4
64
0
1
Order By: Relevance
“…48 Vitamin D was also confirmed to enhance the ability of neutrophils to kill Streptococcus pneumoniae and inhibit excessive inflammation and apoptosis. 49 Similar beneficial effects of vitamin D were observed in paraquat-induced lung fibrosis; vitamin D exhibited its anti-inflammatory effects by decreasing the secretion of pro-inflammatory cytokines. 50 A study of male C57Bl6 mice concluded that supplemental vitamin D in advance can attenuate acute anti-inflammatory actions in the ischemia-reperfusion brain.…”
Section: Discussionmentioning
confidence: 72%
“…48 Vitamin D was also confirmed to enhance the ability of neutrophils to kill Streptococcus pneumoniae and inhibit excessive inflammation and apoptosis. 49 Similar beneficial effects of vitamin D were observed in paraquat-induced lung fibrosis; vitamin D exhibited its anti-inflammatory effects by decreasing the secretion of pro-inflammatory cytokines. 50 A study of male C57Bl6 mice concluded that supplemental vitamin D in advance can attenuate acute anti-inflammatory actions in the ischemia-reperfusion brain.…”
Section: Discussionmentioning
confidence: 72%
“…(264) Studies aimed at identifying a mechanistic basis for this relationship have identified positive correlations between vitamin D status and both the frequency of FoxP3 + regulatory T cells and levels of the anti-inflammatory cytokine IL-10 in the airways of patients with asthma, (172,265) consistent with the capacity of 1,25D to drive differentiation of CD4 + T cell populations in vitro. (126,172) Effects on other types of cells present in the airway may also partly explain these relationships: For example, 1,25D suppresses production of IgE by B lymphocytes (266) and of inflammatory cytokines by neutrophils, (76) but promotes epithelial cell secretion of anti-inflammatory ST2, which blocks mast cell priming by IL-33. (267) Notably, 1,25D also augments the sensitivity of both T cells and monocytes to the anti-inflammatory activity of corticosteroids, which are a mainstay of treatment of this disease.…”
Section: Airway Diseasementioning
confidence: 99%
“…Long-term follow-up of these patients is eagerly awaited. Liu et al 2006-Handsottir et al 2010-Beard et al 2011-Fabri et al 2011-Ruiter et al 2015-Ethier et al 2016 M A N U S C R I P T A C C E P T E D Liu et al 2006-Fabri et al 2011-Lan et al 2014-Xystrakis et al 2006-Nanzer et al 2014-Chambers et al 2015 reduced pro-inflammatory cytokine production by neutrophils but with enhanced anti-bacterial activity -Takahashi et al 2002-Subramanian et al 2017 …”
Section: Accepted Manuscriptmentioning
confidence: 99%